2013
DOI: 10.1111/1440-1681.12053
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events following statin–fenofibrate therapy versus statin alone: A meta‐analysis of randomized controlled trials

Abstract: The combination of fenofibrate with statins is a beneficial therapeutic option for patients with mixed dyslipidaemia, but concerns about adverse events (AEs) make physicians reluctant to use this combination therapy. Medline, Embase and the Cochrane Library were searched to identify 13 randomized controlled trials, involving 7712 patients, of statin-fenofibrate therapy versus statin alone for review. There were significant decreases in low-density lipoprotein-cholesterol, triglycerides and total cholesterol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
(153 reference statements)
1
10
0
Order By: Relevance
“…In the ACCORD study, combination therapy with fenofibrate and simvastatin was associated with a greater effect on TG (−22% vs. −9% for combination therapy vs. statin monotherapy, respectively), HDL‐C (+8% vs. +6%) and TC (−13% vs. −12%) but not LDL‐C . The ACCORD results are consistent with the findings of a recent meta‐analysis showing a greater effect of statin‐fibrate combination therapy compared with statin monotherapy on all major components of the plasma lipid profile (TG, HDL‐C, LDL‐C and TC) .…”
Section: Pparα Agonistssupporting
confidence: 87%
See 1 more Smart Citation
“…In the ACCORD study, combination therapy with fenofibrate and simvastatin was associated with a greater effect on TG (−22% vs. −9% for combination therapy vs. statin monotherapy, respectively), HDL‐C (+8% vs. +6%) and TC (−13% vs. −12%) but not LDL‐C . The ACCORD results are consistent with the findings of a recent meta‐analysis showing a greater effect of statin‐fibrate combination therapy compared with statin monotherapy on all major components of the plasma lipid profile (TG, HDL‐C, LDL‐C and TC) .…”
Section: Pparα Agonistssupporting
confidence: 87%
“…Reassuringly, fenofibrate was found to exert renoprotective effects by reducing albuminuria and slowing glomerular filtration rate (GFR) loss in type 2 diabetic patients [80]. The results of two meta-analyses of randomized controlled trials also showed that the combination of fibrates and statins is as well tolerated as statin monotherapy [75,102]. As referred to earlier, fibrates have been shown to increase serum creatinine levels, but this increase does not apparently reflect nephrotoxicity nor is associated with any adverse renal outcome [84].…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Fenofibrate appears to be safer than gemfibrozil because renal excretion of statins appears to be significantly inhibited by gemfibrozil but not by fenofibrate . Meta‐analyses of randomized trials have found no increase in muscle or tendon‐related adverse events in patients taking fenofibrate plus a statin compared with a statin alone . Studies have also failed to show an increase in the incidence of myopathy or tendinopathy in patients with combined hyperlipidemia who were prescribed pravastatin plus gemfibrozil …”
Section: Discussionmentioning
confidence: 99%
“…15,16 Metaanalyses of randomized trials have found no increase in muscle or tendon-related adverse events in patients taking fenofibrate plus a statin compared with a statin alone. 17,18 Studies have also failed to show an increase in the incidence of myopathy or tendinopathy in patients with combined hyperlipidemia who were prescribed pravastatin plus gemfibrozil. 19 Although myopathy and myositis are common adverse outcomes, tendon rupture remains a seldom reported entity of statin-gemfibrozil combination use.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven (58 %) of patients completing the study were taking cholesterol-lowering medications, including various statins and fenofibrate. These drugs are known to cause liver dysfunction [37], although it should be noted that all patients had normal liver function at baseline.…”
Section: Limitations Of Studymentioning
confidence: 98%